Agronomic Characteristics of Three Superior Varieties of Rice Plants (Oryza sativa L. ) At Different Planting Distances in the System of Rice Intensification (SRI) Pattern System - Yunny Mustika Sucy; Laila Nazirah; Jamidi; Baidhawi; Hafifah (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
The increasing population necessitates a corresponding rise in rice production each year, a condition significantly influenced by cultivation practices and the application of technology. This study aims to evaluate the agronomic characteristics of three superior rice varieties at different planting distances within the System of Rice Intensification (SRI) framework. The research will be conducted in Geulumpang Payong Village, Jeumpa District, Bireuen Regency, at an altitude of approximately 0 to 969 meters above sea level (masl) from August to November 2024. This study employed a split-plot design (RPT) experimental method within a randomized block design (RAK). Two factors were tested: varieties (Ciherang, Inpari 49, and Mustajab) and planting distances (25 cm x 25 cm as the control, 25 cm x 30 cm, 30 cm x 30 cm, and 35 cm x 35 cm). Consequently, 12 treatment combinations were established, with each treatment replicated three times, resulting in a total of 36 experimental units. Each plot contained four research plants, leading to a total of 144 plants. The data obtained from the research were statistically analyzed using the F-test with SAS V9.12 software. If the results of the analysis of variance indicated significant differences at the 5% level, the Duncan Multiple Range Test (DMRT) was conducted. The results suggested that the variety had a considerable influence on the parameters of plant height and the number of leaves. In contrast, leaf area, root length, and the number of tillers did not show significant effects. In terms of planting distance, the number of leaves and tillers was significantly affected, while plant height, leaf area, and root length did not exhibit significant changes. The interaction between the two factors had a substantial impact on the number of leaves, while plant height, leaf area, root length, and the number of tillers showed no significant effects. The Ciherang variety, combined with a planting distance of 30 cm x 30 cm, emerged as the most effective treatment, indicating it was the optimal condition in this study.